2008
DOI: 10.1614/ipsm-07-008.1
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Western Juniper (Juniperus occidentalis) and Understory Vegetation

Abstract: Western juniper has been actively invading sagebrush plant communities for about 130 yr. Western juniper canopy cover generally increases as western juniper invades sagebrush steppe communities and succession progresses toward a western juniper woodland. Our goal was to estimate the impact of juniper invasion and canopy increase on understory vegetation structure and productivity on 101 sites in northeastern California. The primary objectives of this study were to: (1) examine the influence of increasing weste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 22 publications
2
20
1
Order By: Relevance
“…Our results also corroborate other studies reporting that conifer removal improves habitat quality for sage‐grouse or leads to an increase in sage‐grouse use (Commons et al , Coultrap et al , Frey et al , Roundy et al ). Coultrap et al () found that removing junipers from the landscape resulted in increased grass cover and herbaceous productivity and reduced bare ground.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results also corroborate other studies reporting that conifer removal improves habitat quality for sage‐grouse or leads to an increase in sage‐grouse use (Commons et al , Coultrap et al , Frey et al , Roundy et al ). Coultrap et al () found that removing junipers from the landscape resulted in increased grass cover and herbaceous productivity and reduced bare ground.…”
Section: Discussionsupporting
confidence: 92%
“…Our results also corroborate other studies reporting that conifer removal improves habitat quality for sage‐grouse or leads to an increase in sage‐grouse use (Commons et al , Coultrap et al , Frey et al , Roundy et al ). Coultrap et al () found that removing junipers from the landscape resulted in increased grass cover and herbaceous productivity and reduced bare ground. Roundy et al () demonstrated that shrub and perennial grass cover can be maintained when PJ woodlands are removed before displacing desired understory species (Phases I and II), but that treatments implemented when PJ was the dominate vegetation (Phase III) resulted in herbaceous‐dominated plant communities (Miller ).…”
Section: Discussionsupporting
confidence: 92%
“…Condensed tannins and volatile oil in redberry juniper can affect the animal and rumen function (Kumar and Singh, 1984;McIntosh et al, 2003). If DDGS and redberry juniper can effectively be used in lamb feedlot diets, it would not only reduce sheep production costs but may ultimately result in greater rangeland forage production and ecosystem health due to greater removal of juniper trees (Coultrap et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Intensive grazing, reduced fire occurrence, and favorable wetter climate conditions have all been cited as reasons for the vast juniper expansion observed in the late 19th and early 20th century [3,5].Juniper expansion is a concern in many rangeland areas as it may lead to reduced water availability for other types of vegetation. Increased juniper canopy cover has been associated with increased bare ground and decreased shrub, forb, and grass cover [6] and reductions in vegetation production and diversity [7]. Several studies [6,[8][9][10][11] have addressed the impacts of juniper expansion on ecological and hydrological processes.…”
mentioning
confidence: 99%
“…Increased juniper canopy cover has been associated with increased bare ground and decreased shrub, forb, and grass cover [6] and reductions in vegetation production and diversity [7]. Several studies [6,[8][9][10][11] have addressed the impacts of juniper expansion on ecological and hydrological processes. These impacts include increased erosion and runoff [12][13][14] and decreased soil moisture [8] typically associated with shifts in vegetation cover [2,12,15], particularly with increased bare ground in intercanopy locations [16].The use of ground-based techniques to assess vegetation characteristics is limited to the resources available and normally includes an aggregate of data collected at point specific locations.…”
mentioning
confidence: 99%